2002
DOI: 10.1007/s11745-002-0878-2
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Tocopheryl quinone stimulates apoptosis in drug‐sensitive and multidrug‐resistant cancer cells

Abstract: Chemotherapy-induced cell death is linked to apoptosis, and there is increasing evidence that multidrug-resistance in cancer cells may be the result of a decrease in the ability of a cell to initiate apoptosis in response to cytotoxic agents. In previous studies, we synthesized two classes of electrophilic tocopheryl quinones (TQ), nonarylating alpha-TQ and arylating gamma- and delta-TQ, and found that gamma- and delta-TQ, but not alpha-TQ, were highly cytotoxic in human acute lymphoblastic leukemia cells (CEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 46 publications
7
29
0
Order By: Relevance
“…The effect of Á-tocopherol quinone is mainly related to induce apoptosis in leukemia cells and breast cancer cells [124]. Similar results were obtained by Calviello et al [125], who showed that Á-tocopherol quinone induced apoptosis in a dose-and time-dependent manner in cultured human leukemia HL-60 and colon adenocarcinoma WiDr cells, and in murine thymoma cells growing in vivo in ascites form.…”
Section: á-Tocopherol and Cancersupporting
confidence: 78%
“…The effect of Á-tocopherol quinone is mainly related to induce apoptosis in leukemia cells and breast cancer cells [124]. Similar results were obtained by Calviello et al [125], who showed that Á-tocopherol quinone induced apoptosis in a dose-and time-dependent manner in cultured human leukemia HL-60 and colon adenocarcinoma WiDr cells, and in murine thymoma cells growing in vivo in ascites form.…”
Section: á-Tocopherol and Cancersupporting
confidence: 78%
“…Recent studies have suggested that the occurrence of MDR in cancer cells may be the result of a decrease in the ability of the cancer cells to initiate apoptosis in response to cytotoxic agents [28]. Previous studies suggested that overexpression of P-gp via transfection of MDR1 in MCF-7/DOX cells has been shown to significantly decrease the apoptotic response to doxorubicin as compared with its effect in wild-type MCF-7 cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…Failure to repair these DNA lesions can lead to apoptosis (50). On the other hand, γ-and δ-tocopherol quinones generated from γ-and δ-tocopherols, respectively, are cytotoxic arylating electrophiles because they contain an α,β unsaturated carbonyl structure that forms Michael adducts with compounds containing a thiol nucleophilic group, such as glutathione and proteins (51). Whether treatment with PUFA, tocopherols, and DOX leads to the interactions through their alkylating/arylating activities and thereby enhances therapeutic efficacy remains to be studied.…”
Section: Discussionmentioning
confidence: 99%